Characterization of O-antigen delivered by Generalized Modules for Membrane Antigens (GMMA) vaccine candidates against nontyphoidal Salmonella. Issue 3 (11th January 2017) - De Benedetto, G.; Alfini, R.; Cescutti, P.; Caboni, M.; Lanzilao, L.; Necchi, F.; Saul, A.; MacLennan, C.A.; Rondini, S.; Micoli, F.
Abstract: Invasive nontyphoidal Salmonella disease (iNTS) is a leading cause of death and morbidity in Africa. The most common pathogens are Salmonella enterica serovars Typhimurium and Enteritidis. The O-antigen portion of their lipopolysaccharide is a target of protective immunity and vaccines targeting O-antigen are currently in development. Here we investigate the use of Generalized Modules for Membrane Antigens (GMMA) as delivery system for S . Typhimurium and S . Enteritidis O-antigen. Gram-negative bacteria naturally shed outer membrane in a blebbing process. By deletion of the tolR gene, the level of shedding was greatly enhanced. Further genetic modifications were introduced into the GMMA-producing strains in order to reduce reactogenicity, by detoxifying the lipid A moiety of lipopolysaccharide. We found that genetic mutations can impact on expression of O-antigen chains. All S. Enteritidis GMMA characterized had an O-antigen to protein w/w ratio higher than 0.6, while the ratio was 0.7 for S. Typhimurium Δ tolR GMMA, but decreased to less than 0.1 when further mutations for lipid A detoxification were introduced. Changes were also observed in O-antigen chain length and level and/or position of O-acetylation. When tested in mice, the GMMA induced high levels of anti-O-antigen-specific IgG functional antibodies, despite variation in density and O-antigen structural modifications. In conclusion, simplicity of manufacturing process and low costs of production, coupled with encouraging immunogenicity data, make GMMA an attractive strategy to further investigate for the development of a vaccine against iNTS.